2021
DOI: 10.1021/jacs.1c05834
|View full text |Cite
|
Sign up to set email alerts
|

Thioether-Directed NiH-Catalyzed Remote γ-C(sp3)–H Hydroamidation of Alkenes by 1,4,2-Dioxazol-5-ones

Abstract: A NiH-catalyzed thioether-directed cyclometalation strategy is developed to enable remote methylene C–H bond amidation of unactivated alkenes. Due to the preference for five-membered nickelacycle formation, the chain-walking isomerization initiated by the NiH insertion to an alkene can be terminated at the γ-methylene site remote from the alkene moiety. By employing 2,9-dibutyl-1,10-phenanthroline (L4) as the ligand and dioxazolones as the reagent, the amidation occurs at the γ-C­(sp3)–H bonds to afford the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 77 publications
0
48
0
Order By: Relevance
“…This strategy is general and reliable and a large variety of electrophiles can be employed as coupling partners, which allows the stereochemically controlled formation of a variety of carbon–carbon 36 – 55 and carbon–heteroatom 56 65 bonds. Very recently, Seo and Chang 60 , 64 , Yu 63 , and our group 61 have demonstrated that dioxazolones are suitable electrophilic amidating reagents in NiH-catalysed reductive hydroamidation reactions. We envisioned that NiH-catalysed asymmetric hydrofunctionalization could be expanded to the asymmetric hydroamidation of alkenyl boronates with dioxazolones 30 , 60 64 , thus enabling the direct synthesis of a variety of enantioenriched α-aminoboronates which have high potential in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is general and reliable and a large variety of electrophiles can be employed as coupling partners, which allows the stereochemically controlled formation of a variety of carbon–carbon 36 – 55 and carbon–heteroatom 56 65 bonds. Very recently, Seo and Chang 60 , 64 , Yu 63 , and our group 61 have demonstrated that dioxazolones are suitable electrophilic amidating reagents in NiH-catalysed reductive hydroamidation reactions. We envisioned that NiH-catalysed asymmetric hydrofunctionalization could be expanded to the asymmetric hydroamidation of alkenyl boronates with dioxazolones 30 , 60 64 , thus enabling the direct synthesis of a variety of enantioenriched α-aminoboronates which have high potential in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…However, several challenges appeared considerably daunting: (1) undesired competitive cross-coupling between arylboron and electrophilic thiolation reagents, 16 (2) competitive β-H elimination from the alkyl nickel species, and (3) catalyst deactivation caused by sulfur coordination. 17 Herein, we report a Ni-catalyzed regioselective 1,2-carbosulfenylation of homoallylic amines with arylboronic acids and aryl disulfides under the assistance of bidentate PA auxiliary. This new protocol exhibits excellent functional group tolerance and is compatible with α-substituted terminal alkenes and internal alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…However, several challenges appeared considerably daunting: (1) undesired competitive cross-coupling between arylboron and electrophilic thiolation reagents, 16 (2) competitive β-H elimination from the alkyl nickel species, and (3) catalyst deactivation caused by sulfur coordination. 17…”
Section: Introductionmentioning
confidence: 99%
“…Based on precedents, Lu and Fu reported an aminoquinoline directed nickel‐catalyzed alkene hydroalkylation, and adjustments to the reaction ligands resulted in the switching on and off of alkylnickel chain‐walking [11] . In addition, regiodivergent alkene hydroamination/hydroamidation by the chain‐walking of a nickel‐hydride species has also been realized, and ligand‐controlled regiodivergence is state of the art [5b, 12] …”
Section: Introductionmentioning
confidence: 99%